The Effect of Silibinin on Protein Expression Profile in White Adipose Tissue of Obese Mice - Wang, Fei; Chen, Shuchun; Ren, Luping; Wang, Yichao; Li, Zelin; Song, Tiantian; Zhang, He; Yang, Qiwen (Frontiers in Pharmacology, 2020)
Objective：To investigate the effect of silibinin on the protein expression profile of white adipose tissue (WAT) in obese mice by using Tandem Mass Tag (TMT) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Methods: According to experimental requirements, 36 C57BL/6JC mice were randomly divided into normal diet group (WC group), high fat diet group (WF group) and high fat diet + silibinin group (WS group). WS group was intragastrically administered with 54 mg/kg body weight of silibinin, and the WC group and the WF group were intragastrically administered with equal volume of normal saline. Serum samples were collected to detect fasting blood glucose and blood lipids. IPGTT was used to measure the blood glucose value at each time point and calculate the area under the glucose curve. TMT combined with LC-MS/MS were used to study the expression of WAT, and its cellular processes, biological processes, corresponding molecular functions and related network molecular mechanisms were analyzed by bioinformatics. Finally, RT-PCR and LC-MS/MS were used to detect the mRNA and protein expressions of FABP5, Plin4, GPD1 and AGPAT2, respectively. Results: Although silibinin did not reduce the mice's weight, it did improve glucose metabolism. In addition, silibinin decreased the concentration of TC, TG and LDL-C and increased the concentration of HDL-C in the serum of mice. In WF/WS group, there were 182 differentially expressed proteins were up-regulated and 159 were down-regulated. While in WS/WF group, there were 362 differentially expressed proteins were up-regulated and 176 were down-regulated. Further analysis found that these differential proteins are mainly distributed in the peroxisome proliferation-activated receptor (PPAR), lipolysis of fat cells, metabolism of glycerides, oxidative phosphorylation and other signaling pathways, and participate in cell processes and lipid metabolism through catalysis and integration functions. Specifically, silibinin reduced the expression of several key factors such as FABP5, Plin4, GPD1 and AGPTA2. Conclusion: High fat diet (HFD) can increase the expression of lipid synthesis and transport-related proteins and reduce mitochondrial related proteins, thereby increasing lipid synthesis, reducing energy consumption and improving lipid metabolism in vivo. Silibinin can reduce lipid synthesis, increase energy consumption and improve lipid metabolism in mice vivo.